Variation of Potential Yield of Hybrid Population of Robusta coffee (Coffea canepor - Novie Pranata Erdiansyah; Ucu Sumirat; Priyono - (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
The low yield of Robusta coffee in Indonesia may be due to the use of planting materials derived from seeds. The research objective was to determine the variation of Robusta coffee yield wich local propagated by using seeds. The study was conducted in Kaliwining experimental Station of ICCRI (Indonesian Coffee andCocoa Research Institute). There were two populations observed. Number of progeny used in this study were 186 genotypes consisting of two groups from crossesBP 409 x Q 121 with 89 progenies and BP 961 x BP 409 with 81 progenies. The results showed that planting materials from seeds exhibit properties mixed results.Progeny that have the best results (yield more than 2 ton/ha) not more than 5% of the total population. In both populations there is a big difference between the progenythat has high and low yield. Highest yield B population could reach 2,500 kg/ha and the C population reached 2,200 kg/ha. The lowest yield can only produce coffee270 kg/ha in populations B and 120 kg/ha in population C.Key words: Coffea canephora, hybrid, variation, yield